Tingkat Kebersihan Mulut (OHI-S) pada Anak SD Kelas VI Di Desa Wonokromo - Sari Purwanti; Widjijono Widjijono (Universitas Muhammadiyah Yogyakarta, 2008)
Oral hygiene is ones of local factor that has a dominant determination in oral disease. In spite of it, the childrens oral health has an inﬂuence on good behavior to oral health status. The behavior is a very complex any thing that involves internal or external aspect, even psychological and physical. Elementary at the age of II -1 2 years of school student has already able to think rationally and precisely based on their mperience, along with the family support, in order to keep oral hygiene, but in the village, the reality of oral hygiene is still low.Based on those thoughts the aim of this research is to found the level of children oral hygiene at the age of II-I2 years. The object of this research is Wonokromo village in the border city of Kebulnen conﬁne between Sawangan village and Kaliputih village. The samples of this research are I13 students that consist of 56 boys and 57 girls from three elementary schools in Wonokromo village. This research uses cross sectional survey to see the level of Oral hygiene in children in the 6